Preparation and characterization of ultra-lightweight foamed geopolymer (UFG) based on fly ash-metakaolin blends. (20th April 2018) - Wu, Jiandong; Zhang, Zerui; Zhang, Yi; Li, Dongxu
Highlights: Ultra-lightweight foamed geopolymer (UFG) with dry density 150–300 kg/m 3 is prepared. UFG based on fly ash-metakaolin blends is prepared by the chemically foaming. The properties of UFG are investigated by designing and optimizing the components. UFG reveals lower thermal conductivity and desirable compressive strength. Abstract: Ultra-lightweight foamed geopolymer (UFG) based on fly ash-metakaolin blends with its density of between 150 kg/m 3 and 300 kg/m 3 was successfully prepared by the mixed foaming method of chemical foaming. In the present study, the properties and characteristics of UFG were investigated by designing and optimizing the components of fly ash, metakaolin, alkaline activator, foam stabilizer and foaming agent (H2 O2 ), as well as the curing temperature. The results showed that foamed geopolymer with curing age of 7 days presented its dry density between 150 kg/m 3 and 300 kg/m 3, the mean pore size between 0.57 mm and 1.13 mm, the porosity between 71.8% and 84.5%, the thermal conductivity between 0.0622 W/(m·K) and 0.0852 W/(m·K) and the compressive strength between 0.68 MPa and 2.23 MPa, showing better mechanical properties than the traditional portland cement foamed concrete with the same density. It is also found that curing temperature at 55 °C for 12 h seemed to substantially improve the compressive strength of UFG which is 1.91 MPa compared to curing at 25 °C for the same period of time.